Orange II Degradation by Wet Peroxide Oxidation Using Au Nanosized Catalysts: Effect of the Support - Carmen S. D. Rodrigues (2017)
The degradation of Orange II was evaluated by wet peroxide oxidation using gold nanoparticles supported on Fe2O3, TiO2, ZnO, and Al2O3 as catalysts in a slurry batch reactor. Materials were prepared by the same deposition-precipitation method, which yielded well-dispersed nanosized gold particles (2.2-5.5 nm). For comparison, a commercial catalyst (Au/Fe2O3 supplied by the World Gold Council) was used as reference. It was demonstrated that the efficiency of wet peroxide oxidation for the Orange II removal and organics mineralization depends on the type of oxide used and the loading and diameter of gold. The Au/Al2O3 material, with the highest BET surface area, showed the highest turnover frequency value and also higher total organic carbon and Orange II removals. The catalysts were reused for consecutive cycles, with no Au leaching being detected into the solution, demonstrating their high stability. This stability was confirmed by textural and chemical characterization of the fresh and used materials. (c) 2017 American Chemical Society.